Associations of light exposure patterns with sleep among Dutch children: The ABCD cohort study - Stefanopoulou, Magdalini; Ruhé, Naomi; Portengen, Lützen; van Wel, Luuk; Vrijkotte, Tanja G M; Vermeulen, Roel; Huss, Anke (John Wiley and Sons Inc., 2024)
Light exposure affects the circadian system and consequently can affect sleep quality. Only few studies examined this relationship in children. We evaluated associations between light exposure patterns and sleep metrics in children. We measured the sleep parameters of 247 Dutch children, aged between 11 and 13 years and recruited from the ABCD cohort, using actigraphy and sleep records for 7 consecutive nights. Personal light exposures were measured with a light meter during the whole day and night. We applied generalized mixed-effects regression models, adjusted for possible confounders, to evaluate the associations of light exposure patterns on sleep duration, sleep efficiency and sleep-onset delay. In the models mutually adjusted for potential confounders, we found the amount of hours between the first time of bright light in the morning and going to sleep and the duration of bright light to be significantly associated with decreased sleep duration (in min; β: -2.02 [95% confidence interval: -3.84, -0.25], β: -8.39 [95% confidence interval: -16.70, -0.07], respectively) and with shorter sleep-onset delay (odds ratio: 0.88 [95% confidence interval: 0.80, 0.97], odds ratio: 0.40 [95% confidence interval: 0.19, 0.87], respectively). Increased light intensities at night were associated with decreased sleep duration (T2 β: -8.54 [95% confidence interval: -16.88, -0.20], T3 β: -14.83 [95% confidence interval: -28.04, -1.62]), while increased light intensities before going to bed were associated with prolonged sleep onset (odds ratio: 4.02 [95% confidence interval: 2.09, 7.73]). These findings further suggest that children may be able to influence their sleep quality by influencing the light exposure patterns during day and night.
Keywords: accelerometry; children; light exposure; light meter; sleep duration; sleep onset; Cognitive Neuroscience; Behavioral Neuroscience